2002
DOI: 10.1016/s0886-3350(02)01323-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the soft-shell technique in cases with a hard lens nucleus

Abstract: The results suggest that the soft-shell technique is safe and effective in protecting corneal endothelial cells during cataract surgery in patients with a hard lens nucleus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
51
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 13 publications
3
51
0
Order By: Relevance
“…In this study, the density of corneal endothelial cells decreased following cataract surgery when compared with the preoperative numbers in both groups. In previous studies, to analyze the degree of corneal damage following phacoemulsification, the number and density of corneal endothelial cells in a 1 mm 2 area were measured using specular microscopy [16][17][18][19]; however, specular microscopy can only evaluate a small part of the corneal endothelial injury and is therefore insufficient for ascertaining changes in the entire cornea and morphological changes at the incision point. Therefore, based on the central corneal thickness and specular microscopy alone, the data needed for determining the degree of corneal edema following phacoemulsification are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the density of corneal endothelial cells decreased following cataract surgery when compared with the preoperative numbers in both groups. In previous studies, to analyze the degree of corneal damage following phacoemulsification, the number and density of corneal endothelial cells in a 1 mm 2 area were measured using specular microscopy [16][17][18][19]; however, specular microscopy can only evaluate a small part of the corneal endothelial injury and is therefore insufficient for ascertaining changes in the entire cornea and morphological changes at the incision point. Therefore, based on the central corneal thickness and specular microscopy alone, the data needed for determining the degree of corneal edema following phacoemulsification are insufficient.…”
Section: Discussionmentioning
confidence: 99%
“…19,[25][26][27] It is known that endothelial cell survival depends on the type of OVD used. 11,12,15,18 It is unclear whether ECL decreases using phaco chop technique during fluid-based phacoemulsification. Further prospective randomized clinical trials are needed to investigate ECL in different nuclear fragmentation techniques and using different OVD's during water-jet procedure.…”
Section: Discussionmentioning
confidence: 99%
“…The results on mean ECL vary from 0.4 to 27.7% after phacoemulsification, depending on different surgical techniques. 2,[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] In recent years, new surgical procedures have been developed to reduce ECL, such as laserand fluid-based methods. During the latter procedure, short pulses (4 ml) of warmed balanced salt solution liquefy the lens material, while the irrigation fluid surrounds the warmed pulsating fluid allowing cooling of the pulse.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial cell loss after phacoemulsification surgery is well documented. 6,7 Corneal endothelial damage during phacoemulsification is attributed to several factors including excessive duration of phacoemulsification, [8][9][10] localized temperature increase, 11 contact or collision of lens nucleus fragments after turbulent flow of irrigation solution, 12,13 air bubbles, 14,15 and surgical skills. 16 It has also been shown that the generation of free radicals during phacoemulsification can cause adverse effects on the cellular and subcellular levels through diverse mechanisms, one of which is acoustic cavitation.…”
mentioning
confidence: 99%